Current approaches and advance in mantle cell lymphoma treatment - Liu, Yao (Stem Cell Investig, 2015)
Mantle cell lymphoma (MCL) is a set of heterogeneous non-Hodgkin lymphoma characterized by involvement of lymph nodes, spleen, bone marrow and blood. Under conventional treatment, survival time is 4 to 5 years with short remission period and there is still no standard treatment for MCL. In general, a close observation period called “watchful waiting” is used in elderly patients with low-risk slow clinical progress. And intensive chemotherapy including high-dose of cytarabine ± autologous hematopoietic stem cell transplantation (auto-HSCT) is recommended for younger and fit patients. Allogenic stem cell transplantation (allo-SCT) and drugs targeting the cell metabolic pathway, such as bortezomib (NF-κB inhibitor) and lenalidomide (anti-angiogenesis drug), are considerable treatments for relapsed/refractory patients. Clinical trials and less intensive chemotherapy such as R-CHOP (rituximab with cyclophosphamide, hydroxydaunomycin, oncovin and prednisone) and R-bendamustine should be considered for elderly MCL patients who are at intermediate/high risk. Recent clinical trials with ibrutinib (Bruton’s Tyrosine Kinase inhibitor) and temsirolimus (mTOR inhibitor) have shown excellent efficacies in the treatment of MCL. This review will introduce the present status and major therapeutic progress in the treatment of MCL over recent years in order to provide a cutting edge to look into promising clinical progress of MCL.